EMPOWERMENT OF LOCAL INSTITUTIONS FOR TOURISM DEVELOPMENT IN KASEPUHAN SINARRESMI - Rahmawati, Rita; Sastrawan, Berry; Pratidina, Ginung; Virly Apriliyani, Neng; Fitriah, Maria; Hasbiyah, Desi; Tri Ramdhani, Faisal; Rochman, Nur; Syahrudin, Dede; Julaeha, Siti; Yuliana, Yuliana; Adellia Safitri, Liza; Ahmad Shiddiq, Naufal; Rahma Wati, Siti (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
The local institutional conditions of Sirnaresmi Village which have not been managed optimally in developing cultural tourism based on local wisdom as an alternative for other incomes for the community have not been carried out properly due to the resource capacity that has not been optimally managed for the welfare of indigenous peoples. Therefore, empowerment, training and mentoring programs are needed with the aim of increasing local institutional capacity and developing local wisdom-based tourism by providing counseling, training, and mentoring methods. Based on the results of the pre-test and post-test implementation of local institutional empowerment to develop tourism, there was a significant increase both quantitatively and qualitatively. As for the comparison between before and after the training, there was an increase of 30%.